Factores que influyen en el clima organizacional de los docentes de la Universidad Técnica de Cotopaxi. - Ríos Guanoluisa, Diana Elizabeth (2018)
The Organizational Environment is a topic of great importance nowadays that must be analyzed by all the companies and institutions, that is why in this project was realize a study of the factors that influence in the organizational environment of the Technical University of Cotopaxi teachers on Latacunga city, allowing to obtain information on the current situation of the organizational environment of the institution. The research job is based on theoretical bases such as; the types of organizational environment, importance, characteristics and factors that influence it. The study has a quantitative approach, type of descriptive research for the description and analysis of the problem to investigate. The instrument applied was authored by Luc Brunet, which is adaptable for institutions of higher education considering individual, group and organizational factors among which are; autonomy, motivation, sense of belonging, identity, teamwork, leadership, conflict, support, communication, decision making, organizational structure, remuneration, career, recognition and equity. The analysis of the results was executed through the statistical program SPSS and Microsoft Excel; with a study object of 180 teachers. It is concluded that the individual factors positively influence the organizational climate of the teachers while that the group and organizational should improve as they present a regular rating.